Pancasila sebagai dasar negara dan paradigma kehidupan dalam masyarakat Berbangsa dan Bernegara: Peran Pancasila dalam Kehidupan Berbangsa dan Bernegara di Indonesia - hayati, amal (Maliki Interdisciplinary Journal, 2025)
Pancasila plays a fundamental role in shaping the framework of national and state life in Indonesia. As the state ideology, Pancasila serves as the source of all laws, a moral compass, and a guiding principle for national development. This article aims to analyze the meaning and implementation of Pancasila values in the social, political, economic, and cultural contexts of Indonesian society. The research uses a descriptive qualitative approach by examining relevant academic literature and references. The findings reveal that the values of Pancasila remain highly relevant in strengthening national character, building citizens’ moral integrity, and promoting a just and civilized society. Nevertheless, the challenges of globalization and modernization require a revitalized understanding and contextual application of Pancasila’s values. Thus, Pancasila does not merely function as an ideological symbol of the nation, but also serves as a practical guideline in national life that plays an important role in maintaining national unity and encouraging the achievement of social welfare.